2018
DOI: 10.1073/pnas.1818624116
|View full text |Cite
|
Sign up to set email alerts
|

Unregulated antigen-presenting cell activation by T cells breaks self tolerance

Abstract: T cells proliferate vigorously following acute depletion of CD4+ Foxp3+ T regulatory cells [natural Tregs (nTregs)] and also when naive T cells are transferred to syngeneic, nTreg-deficient Rag1−/− hosts. Here, using mice raised in an antigen-free (AF) environment, we show that proliferation in these two situations is directed to self ligands rather than food or commensal antigens. In both situations, the absence of nTregs elevates B7 expression on host dendritic cells (DCs) and enables a small subset of naive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…4 b,c). Together with the previously reported decrease in nucleotide excision repair, both in vitro and in vivo , after long-term exposure to e-cigarette aerosol 36 , 42 , 43 , our data strongly suggest that other mechanisms, rather than an increase in DNA damage repair, contribute to the observed increase in cisplatin resistance.
Figure 4 Exposure to e-cigarette aerosol extracts decreases the expression of DNA damage repair genes.
…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…4 b,c). Together with the previously reported decrease in nucleotide excision repair, both in vitro and in vivo , after long-term exposure to e-cigarette aerosol 36 , 42 , 43 , our data strongly suggest that other mechanisms, rather than an increase in DNA damage repair, contribute to the observed increase in cisplatin resistance.
Figure 4 Exposure to e-cigarette aerosol extracts decreases the expression of DNA damage repair genes.
…”
Section: Resultssupporting
confidence: 85%
“…The majority of cisplatin-induced DNA lesions, intra-strand adducts, and inter-strand crosslinks are removed by nucleotide excision repair. Importantly, we and others have previously reported that long-term exposure to e-cigarette aerosol leads to a decrease in DNA repair capacity in non-cancer cells, due to a decrease in the expression of base excision and nucleotide excision repair enzymes 36 , 42 , 43 . Thus, we investigated whether under the current exposure conditions e-cigarette aerosol alters the expression of XPA, MMS19 , and ERCC1 , genes essential for the removal of cisplatin-induced DNA damage.…”
Section: Resultsmentioning
confidence: 66%
“…As for other forms of tolerance mediated by Tregs, the issue of how these cells regulate the immune response is still controversial (8,48). In addition to release of inhibitory mediators such as IL-10 and TGFβ, Tregs are now known to function in part by reducing the levels of B7 (CD80 and CD86) costimulatory molecules on DCs by CTLA4-mediated transendocytosis (49)(50)(51), a process that can be accentuated by increasing Treg numbers. Thus, other workers reported that increasing Treg numbers by injection of the same IL-2/mab complexes used here caused a prominent decrease in the background level of B7 on DCs (32).…”
Section: Discussionmentioning
confidence: 99%
“…Most of naïve T cells circulating in the periphery have been selected during thymic selection to be weakly autoreactive and continuously engage their TCR with self-peptide MHC complexes expressed by cDCs to maintain a state of heightened Ag sensitivity to foreign Ags (25)(26)(27). It has been argued that the need for such weak "tonic" TCR signals creates a potential threat that cannot be constrained by negative regulatory mechanisms intrinsic to conventional naïve T cells and that such risk is buffered by the suppressive action of T reg cells (28,29). Accordingly, after homeostatic maturation, cDCs serve as informationtransmission platform favoring the encounter of T reg cells and naïve T cells (30).…”
Section: Discussionmentioning
confidence: 99%